2013
DOI: 10.1128/aem.02749-12
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Borrelia burgdorferi Sensu Stricto ospC Alleles Associated with Human Lyme Borreliosis Worldwide in Non-Human-Biting Tick Ixodes affinis and Rodent Hosts in Southeastern United States

Abstract: Here we present the first expanded analysis of ospC alleles of B. burgdorferi strains from the southeastern United States with respect to their relatedness to strains from other North American and European localities. We demonstrate that ospC genotypes commonly associated with human Lyme disease in European and North American regions where the disease is endemic were detected in B. burgdorferi strains isolated from the non-human-biting tick Ixodes affinis and rodent hosts in the southeastern United States. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 73 publications
2
40
0
2
Order By: Relevance
“…Our results support the association of B. burgdorferi with Lyme arthritis [15,16]. The confirmed ability of ospC type L strains to disseminate into vertebrate host tissues in the same manner as invasive ospC type B strains, known to be responsible for severe disease in humans worldwide, increases the possible disease risk to humans in the southeastern U.S.A., the region, where studied strains are widely distributed [5]. …”
Section: Results and Conclusionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our results support the association of B. burgdorferi with Lyme arthritis [15,16]. The confirmed ability of ospC type L strains to disseminate into vertebrate host tissues in the same manner as invasive ospC type B strains, known to be responsible for severe disease in humans worldwide, increases the possible disease risk to humans in the southeastern U.S.A., the region, where studied strains are widely distributed [5]. …”
Section: Results and Conclusionsupporting
confidence: 71%
“…As the tick vectors and reservoir hosts differ significantly between the northeastern and southeastern regions, it is highly possible that B. burgdorferi strains that cause LD in both areas will differ as well. Our previous research showed that of the 4 ospC types, B, G, H and N that have been detected in LD patients in the northeastern and midwestern U.S.A., 3 types, B, G, and H, at a lower rate, are widely distributed in the southeastern United States [5]. While OspC type B is associated with severe LD around the world [6,7], ospC types H and G are commonly detected in tissues at disseminated sites of LD patients from the northeastern and midwestern U.S.A. [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…111 B burgdorferi has been isolated from Ixodes affinis and rodent hosts in the coastal areas of the southern United States, but it is not clear how often humans may be bitten by these ticks and infected with B burgdorferi. 112 Investigations by Clark and colleagues 29,53 suggest other B burgdorferi s.l. species may cause disease in people in southern states, although their findings will have to be confirmed by others (see Ref.…”
Section: Rst Genotypementioning
confidence: 96%
“…Por lo tanto, los perros y los humanos pueden ser hospederos accidentales de patógenos. Ixodes affinis por lo general no parasita a los humanos (Rudenko et al, 2012); sin embargo, Allan (2001) observó a esta especie alimentándose de un humano, por lo que se necesitan estudios adicionales para confirmar el papel del humano como hospedero accidental de I. affinis.…”
Section: Resultados Y Discusiónunclassified